2015
DOI: 10.2322/tastj.12.89
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Evaluation of CO<sub>2</sub>-N<sub>2</sub>-Ar Plasma Flows Using the Area Intensity Method

Abstract: The aim of this research is to investigate the thermal nonequilibrium state of CO2-N2-Ar plasma flows generated in an arc-heated wind tunnel using spectroscopic analysis. An area intensity method that uses molecular band spectra is applied to accurately evaluate the thermal nonequilibrium state of the plasma flows. The radiation from CO2-N2-Ar arc plasma flows around a disk model is observed using spectroscopic measurements. The flow temperatures are evaluated by applying the area intensity method to the CN Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…These errors significantly increased when the analysis is performed for spectra with low C 2 Swan band peak intensity, away from the axis of symmetry. In such cases, the background continuum influences differently each of the C 2 Swan peaks, in a similar way as reported in other measurements in CO 2 at lower pressures [33]. For this reason, the continuum hinders the accuracy of spectrum fitting analysis when performed for an entire vibrational sequence in space-resolved measurements.…”
Section: Time-and-space-resolved Spectroscopic Measurementssupporting
confidence: 64%
See 1 more Smart Citation
“…These errors significantly increased when the analysis is performed for spectra with low C 2 Swan band peak intensity, away from the axis of symmetry. In such cases, the background continuum influences differently each of the C 2 Swan peaks, in a similar way as reported in other measurements in CO 2 at lower pressures [33]. For this reason, the continuum hinders the accuracy of spectrum fitting analysis when performed for an entire vibrational sequence in space-resolved measurements.…”
Section: Time-and-space-resolved Spectroscopic Measurementssupporting
confidence: 64%
“…It requires additionally that the radiating specie density is known and that the plasma is optically thin. The (0,0) transition peak at 516.5 nm of the ∆v = 0 sequence of the C 2 Swan band is used here as it has been previously used for the estimation of T r in CO 2 low pressure plasmas [33]. To also reduce the effect of the continuum, the peak baseline is taken from the minimum near the bandhead instead of the zero reference of the instrument [33].…”
Section: Time-and-space-resolved Spectroscopic Measurementsmentioning
confidence: 99%
“…3) In addition, the authors have investigated the thermal nonequilibrium state of CO2-N2-Ar and CO2-Ar plasma flows. 4,5) In these studies, the area intensity method that uses the molecular band spectra of CN and C2 was newly applied to accurately evaluate the thermal nonequilibrium state of the plasma flows. The result showed that the thermochemical state of the plasma flows was in the vibrational nonequilbirum state along the stagnation streamline around a blunt body.…”
Section: Introductionmentioning
confidence: 99%